MODIFY RISK FACTORS PADA KEJADIAN PENYAKIT JANTUNG KORONER DI RUMAH SAKIT UMUM DAERAH TUGUREJO SEMARANG (Nursing Care Journal, 2022)
Coronary artery disease is a condition of fatty deposits in the coronary arterial vessels of the heart that inhibit blood flow to the heart. Risk factors for coronary heart disease consist of factors that can be modified (history of the disease, lifestyle) and non-modifiable (genetic). The existence of a history of hypertension, diabetes mellitus and smoking lifestyle can affect the incidence of coronary heart disease. The purpose of the research was to analyze modify risk factors in the incidence of coronary heart disease at RSUD Tugurejo Semarang. Research design is quantitative research with a retrospective descriptive design. The population in this research was data on patients with coronary heart disease in the last 1 year of the 2020 period. The population in RSUD Tugurejo Semarang is 242 people. The sampling technique used is quota sampling of 151 respondents. The results of bivariate analysis obtained factors that affect the incidence of coronary heart disease, namely a history of hypertension and diabetes mellitus. There is no association between smoking lifestyle, obesity and physical activity to the incidence of coronary heart disease. The results of multivariate analysis obtained a more dominant risk factor for coronary heart disease events, namely a history of hypertension with a value of p-value < 0.05. Hypertension becomes the dominant factor because high blood pressure continuously causes damage to the arterial vascular system slowly. It is also aggravated the presence of fatty deposits on the walls of blood vessels. This increases the risk of coronary heart disease. Recommendations from the results of this study for further research is that it is hoped that this research can be used as literature on the dominant risk factor data for heart disease that occurs in hospitals.